2018
DOI: 10.1016/j.coph.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of resistance in estrogen receptor positive breast cancer: overcoming resistance to tamoxifen/aromatase inhibitors

Abstract: Several mechanisms of resistance have been identified, underscoring the complex nature of estrogen receptor (ER) signaling and the many connections between this pathway and other essential signaling pathways in breast cancer cells. Many therapeutic targets of cell signaling and cell cycle pathways have met success with endocrine therapy and remain an ongoing area of investigation. This review focuses on two major pathways that have recently emerged as important opportunities for therapeutic intervention in end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
90
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 57 publications
1
90
0
1
Order By: Relevance
“…The phosphatidylinositol 3-kinase/AKT/mammalian target of the rapamycin (PI3K/AKT/mTOR) pathway is a key signaling driver of cellular proliferation and survival of cancer cells. Dysregulation and activation of this pathway can drive tumorigenesis of ER+/HER2− breast cancers and is associated with resistance to anti-estrogen-targeted therapies [17,18]. Previous studies in our laboratory have demonstrated that inhibitors of the PI3K/AKT/mTOR pathway have selective activity in ER+ breast cancer cell lines carrying activating mutations in PIK3CA [19,20].…”
Section: Introductionmentioning
confidence: 96%
“…The phosphatidylinositol 3-kinase/AKT/mammalian target of the rapamycin (PI3K/AKT/mTOR) pathway is a key signaling driver of cellular proliferation and survival of cancer cells. Dysregulation and activation of this pathway can drive tumorigenesis of ER+/HER2− breast cancers and is associated with resistance to anti-estrogen-targeted therapies [17,18]. Previous studies in our laboratory have demonstrated that inhibitors of the PI3K/AKT/mTOR pathway have selective activity in ER+ breast cancer cell lines carrying activating mutations in PIK3CA [19,20].…”
Section: Introductionmentioning
confidence: 96%
“…Despite its wide use for the treatment of breast cancer, a third of patients with breast cancer develop resistance to tamoxifen, which results in tumor progression (24). Additionally, TAMR breast cancer is more prone to invasion and metastasis (6), thus identifying the mechanisms underlying drug-resistant tumor metastasis, as well as novel therapeutic strategies is critical to improve patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…The observed endocrine resistance in a proportion of patients with this kind of cancer can be at least partly explained by the dysregulation in the expression of miRNAs/lncRNAs. Resistance to endocrine therapies is complicated process that involves epigenetic alterations in the ESR1 gene, alternative splicing events, post-translational alterations and altered recruitment of co-regulators of ER; it also affects the tumor milieu and several other mechanisms [120]. Almost all aspects of this complex process can be modulated by non-coding RNAs.…”
Section: Discussionmentioning
confidence: 99%